Systematic analysis of the genus Eriocaulon L. in India based on molecular and morphological evidence. Issue 7 (3rd October 2021) - Darshetkar, Ashwini M.; Datar, Mandar N.; Prabhukumar, K.M.; Kim, Soo-Yong; Tamhankar, Shubhada; Choudhary, Ritesh Kumar
Abstract : The present study is the first-ever comprehensive molecular systematic study of Indian Eriocaulon species based on the critical appraisal of the freshly collected 552 accessions of 66 Eriocaulon spp. The genus Eriocaulon L. (Eriocaulaceae) is one of the most diverse genera of Eriocaulaceae and around one-quarter of the world's representation is in India. The taxonomy of the genus has been challenging due to high intraspecific and low interspecific variation. With about 70% of Indian species endemic to the country, sparse representation in earlier phylogenetic studies did not provide phylogenetic resolution of Indian species. A critical analysis of morphology including microscopic seed surface characters of 55 species is presented here for the first time. Phylogenetic analyses based on ITS and trnL–F data yielded three major clades of Indian Eriocaulon species. Based on the morphological and molecular data, Eriocaulon baramaticum, E. govindiana, E. gulnarparianum, E. idukkianum, E . maharashtrense and E. pradeepii have been synonymized. Also, Eriocaulon rhodae has been reinstated. Molecular data exhibited little congruence with the earlier available taxonomic treatments for Indian species. Several morphological characters were mapped onto a phylogeny and none were found to characterize monophyletic groups.